Socio-demographic and clinical factors contributing to smoking cessation among men: a four-year follow up study of the Korean Health Panel Survey - Joo Eun Lee; Eun-Cheol Park; Sung Youn Chun; Hye Ki Park; Tae Hyun Kim (BMC, 2016)
Abstract Background To examine factors contributing to smoking cessation among male smokers, we looked at how socio-demographic and clinical characteristics influence stopping smoking with passage of time. Methods Data from the Korea Health Panel during 2009-2012 were used. In 2009 a total of 2,941 smokers were followed up until 2012. Statistical analysis using a generalized linear mixed model was performed for all smokers, and a subgroup analysis was also performed to determine whether individual characteristics influence smoking cessation differently based on health condition. Results Male smokers who have married or graduated college or above were more likely to succeed in smoking cessation. Those with chronic disease(s) were also more likely to quit smoking than those without. Among those without chronic disease, higher education showed significant association with smoking cessation, however, being married or ever married showed significant association with smoking cessation among those with chronic disease. Conclusions The finding that higher education helped smokers without chronic disease succeed in smoking cessation suggests that a smoking cessation campaign should focus on those with lower education. In addition, quit smoking programs may be particularly helpful for male smokers with chronic disease(s) who have never married.